2008
DOI: 10.1126/science.1162844
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Hyperactive Neurons Near Amyloid Plaques in a Mouse Model of Alzheimer's Disease

Abstract: The neurodegeneration observed in Alzheimer's disease has been associated with synaptic dismantling and progressive decrease in neuronal activity. We tested this hypothesis in vivo by using two-photon Ca2+ imaging in a mouse model of Alzheimer's disease. Although a decrease in neuronal activity was seen in 29% of layer 2/3 cortical neurons, 21% of neurons displayed an unexpected increase in the frequency of spontaneous Ca2+ transients. These "hyperactive" neurons were found exclusively near the plaques of amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

87
917
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 942 publications
(1,060 citation statements)
references
References 40 publications
87
917
4
3
Order By: Relevance
“…In this study, we used 6-to 8-mo-old APP23xPS45 transgenic mice that exhibit severe cerebral Aβ pathology, neuritic and glial cytopathology, and learning and memory deficits (10,11). In accordance with a previous protocol (9), we treated the plaque-bearing mice for 6-8 wk with food pellets containing the BACE inhibitor NB-360 (0.25 mg/g of food, corresponding to a daily oral dose of 20 μmol/kg) or control pellets without the inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used 6-to 8-mo-old APP23xPS45 transgenic mice that exhibit severe cerebral Aβ pathology, neuritic and glial cytopathology, and learning and memory deficits (10,11). In accordance with a previous protocol (9), we treated the plaque-bearing mice for 6-8 wk with food pellets containing the BACE inhibitor NB-360 (0.25 mg/g of food, corresponding to a daily oral dose of 20 μmol/kg) or control pellets without the inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether the treatment with NB-360 had any beneficial effects on learning and memory deficits in the aged transgenic mice, we trained mice in a water maze task to find a fixed, visible platform (10,11) (Fig. 4A).…”
Section: Significancementioning
confidence: 99%
“…We report here a third system involving presynaptic neurons. Presynaptic neuronal Ca 2+ hyperactivation has been reported to occur near amyloid plaques in AD model mice (44). Interestingly, such hyperactivation of neurons in hippocampus has been associated with the cortical thinning in mild cognitive impairment patients and has been considered to be an early indicator of AD-related neurodegeneration (45).…”
Section: Discussionmentioning
confidence: 99%
“…CTF, C terminal fragment; sAPP, soluble APP; BACE, b-site APP cleavage enzyme, ADAM, a disintegrin and metalloprotease, TACE, tumor necrosis factor a cleavage enzyme; Aph1, anterior pharynx defective; Pen, presenilin enhancer. plaques found that excitability was increased in the areas of cortex adjacent to plaques relative to areas further away (37,38). However, more research is needed before it can be concluded that Ab plaque is responsible for seizures.…”
Section: Pass the Salt: Mechanisms Of Seizures In Mouse Models Of Ad mentioning
confidence: 99%